Crop Development of Soybean Varieties: Mycorrizhal Application On Coastal Sandy Soils - Pusparani, Syafina (Food, Agriculture and Natural Resources - NETWORKS, 2025)
This study evaluated the growth and yield of three soybean varieties in response to mycorrhizal dosage on coastal sandy soil in Purworejo Regency, Central Java, Indonesia. The experiment employed a Factorial Randomized Complete Block Design (RCBD) with Split-Plot analysis for growth variables. The first factor was soybean varieties–Grobogan (V1), Burangrang (V2) and Agro Mulyo (V3). The second factor was mycorrhizal dosages–0 g per plant (D1), 1 g per plant (D2) and 2 g per plant (D3). Each of the nine combinations was replicated three times. The observed variables ware Crop Growth Rate (CGR); Relative Growth Rate (RGR); Net Assimilation Rate (NAR); Chlorophyll a (Chl a); Chlorophyll b (Chl b); Harvest Index; Pods per Plant; Dry Weight of Seed per Plant (DSP); Dry Weight of Seed per Sample Area (DSS); Dry Weight of Seed per Hectare (DSH), and Protein Content (PC). Data were analyzed using Analysis of Variance (ANOVA), and significant differences were further examined using post hoc analysis by the Duncan Multiple Range Test (DMRT). The three soybean varieties showed differences in their CGR. The CGR at 59 days after planting showed variations among the three varieties. The most notable increase in CGR was observed in the Burangrang variety between 59 and 73 days after planting. Burangrang also produced the highest average number of pods per plant (67.71 pods), due to vigorous growth and optimal branching (1–2 branches per plant). However, the highest protein content at 42.88% was found in the Grobogan variety by 2 g per plant of mycorrhiza dosage.